Motion-induced compression of perceived numerosity - Michele Fornaciai (Nature Portfolio, 2018)
Abstract It has been recently proposed that space, time, and number might share a common representation in the brain. Evidence supporting this idea comes from adaptation studies demonstrating that prolonged exposure to a given stimulus feature distorts the perception of different characteristics. For example, visual motion adaptation affects both perceived position and duration of subsequent stimuli presented in the adapted location. Here, we tested whether motion adaptation also affects perceived numerosity, by testing the effect of adaptation to translating or rotating stimuli moving either at high (20 Hz) or low (5 Hz) speed. Adaptation to fast translational motion yielded a robust reduction in the apparent numerosity of the adapted stimulus (~25%) while adaptation to slow translational or circular motion (either 20 Hz or 5 Hz) yielded a weaker but still significant compression. Control experiments suggested that none of these results could be accounted for in terms of stimulus masking. Taken together, our results are consistent with the extant literature supporting the idea of a generalized magnitude system underlying the representation of numerosity, space and time via common metrics. However, as changes in perceived numerosity co-varied with both adapting motion profile and speed, our evidence also suggests complex and asymmetric interactions between different magnitude representations.